Respostas
respondido por:
0
a₁ = 23
r = 6
n = 9
a₁₀ = a₁ + (n - 1) * r
a₁₀ = 23 + (9 - 1) * 6
a₁₀ = 23 + 8 * 6
a₁₀ = 23 + 48
a₁₀ = 71
Espero ter ajudado. Valeu!
r = 6
n = 9
a₁₀ = a₁ + (n - 1) * r
a₁₀ = 23 + (9 - 1) * 6
a₁₀ = 23 + 8 * 6
a₁₀ = 23 + 48
a₁₀ = 71
Espero ter ajudado. Valeu!
respondido por:
0
a1 = 23
r = 6
===
Nono termo = a9
an = a1 + ( n -1 ) . r
a9 = 23 + ( 9 -1 ) . 6
a9 = 23 + 8 . 6
a9 = 23 + 48
a9 = 71
r = 6
===
Nono termo = a9
an = a1 + ( n -1 ) . r
a9 = 23 + ( 9 -1 ) . 6
a9 = 23 + 8 . 6
a9 = 23 + 48
a9 = 71
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás